2002
DOI: 10.1038/nature01268
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the inositol 1,4,5-trisphosphate receptor binding core in complex with its ligand

Abstract: In a variety of cells, the Ca2+ signalling process is mediated by the endoplasmic-reticulum-membrane-associated Ca2+ release channel, inositol 1,4,5-trisphosphate (InsP3) receptor (InsP3R). Being ubiquitous and present in organisms ranging from humans to Caenorhabditis elegans, InsP3R has a vital role in the control of cellular and physiological processes as diverse as cell division, cell proliferation, apoptosis, fertilization, development, behaviour, memory and learning. Mouse type I InsP3R (InsP3R1), found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
380
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(394 citation statements)
references
References 28 publications
13
380
0
1
Order By: Relevance
“…Because of the absence of a high-resolution structure for any domain in RyR1, we used comparative modeling to further interpret the structure. Using sequence and structural analysis (16)(17)(18), a structural homolog was identified with high confidence for two segments at the RyR1 N terminus: the ligand-binding suppressor domain [Protein Data Bank (PDB) ID code 1XZZ (19)] for residues Q12-S207 and the IP 3 -binding core region [PDB ID code 1N4K (20)] of the type 1 inositol 1,4,5-trisphosphate receptor (IP 3 R1) for residues G216-Y565 (Fig. 3A and Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the absence of a high-resolution structure for any domain in RyR1, we used comparative modeling to further interpret the structure. Using sequence and structural analysis (16)(17)(18), a structural homolog was identified with high confidence for two segments at the RyR1 N terminus: the ligand-binding suppressor domain [Protein Data Bank (PDB) ID code 1XZZ (19)] for residues Q12-S207 and the IP 3 -binding core region [PDB ID code 1N4K (20)] of the type 1 inositol 1,4,5-trisphosphate receptor (IP 3 R1) for residues G216-Y565 (Fig. 3A and Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Residues G216 -Y565 share a fold with the IP 3-binding core of the IP3R1 channel (PDB ID code 1N4K, sequence identity 16%) (Figs. S2 and S3) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Stimulation of IP 3 R by cytosolic Ca 2þ is universally observed even with purified IP 3 R reconstituted into lipid bilayers (Ferris et al 1989;Hirota et al 1995;Michikawa et al 1999), suggesting that this essential Ca 2þ -binding site probably resides within the primary sequence of the IP 3 R. At least seven cytosolic Ca 2þ -binding sites have been identified within IP 3 R1 (Sienaert et al 1996;Sienaert et al 1997), but the physiological relevance of these sites is unresolved. Two of the sites (residues 304-381 and 378-450) are within the IP 3 -binding core, for which there is a high-resolution structure (Bosanac et al 2002). This structure shows two surface-exposed clusters of acidic residues that overlap with residues in the second N-terminal Ca 2þ -binding region.…”
Section: Regulation Of Ip 3 Receptors By Ca 2þ and Ipmentioning
confidence: 99%
“…It is noteworthy that neither of the immediate products of IP 3 metabolism, IP 2 and IP 4 , binds to the IBC; both metabolic pathways are therefore effective means of terminating activation of IP 3 R by IP 3 . An atomic structure of the IBC with IP 3 bound (Bosanac et al 2002) shows IP 3 held within a clam-like structure in which the phosphate groups of IP 3 are coordinated by basic residues (Fig. 3A).…”
Section: Structural Determinants Of Ip 3 R Activationmentioning
confidence: 99%
“…The recent solving of the crystal structure of the type I IP 3 R LBD has revealed that it consists of an N-terminal ␤-domain forming a ␤-trefoil fold, hinged to an all-helical C-terminal domain containing three armadillo-repeat-like structures (26) (Fig. 5A).…”
Section: The All-helical Fragment Of the Ip3r Lbd Is Sufficient To Opmentioning
confidence: 99%